The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1186/s12890-017-0381-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation for avian influenza A (H7N9) patient with acute respiratory distress syndrome: a case report and short literature review

Abstract: BackgroundExtracorporeal membrane oxygenation (ECMO) is performed as an acceptable life-saving bridging procedure in patients with severe acute respiratory distress syndrome (ARDS).To patients with avian influenza A (H7N9)-associated ARDS, ECMO could be adopted as a feasible therapeutic solution. We present our successful experience with ECMO utilized in a respiratory failure patient with H7N9 infection.Case presentationA 44 years-old female with H7N9-induced ARDS was admitted to intensive care unit (ICU) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The clinical, virological, immunological, and epidemiological features of human cases have been reported [ 8 , 16 , 24 , 52 ]. To treat such patients, immediate use of antiviral drugs and steroids is very common in the ICU, as is the use of MV or ECMO when necessary [ 2 , 36 ]. We also observed that epithelial barrier function was severely impaired in the lung biopsy specimen from a patient with laboratory-confirmed H7N9 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical, virological, immunological, and epidemiological features of human cases have been reported [ 8 , 16 , 24 , 52 ]. To treat such patients, immediate use of antiviral drugs and steroids is very common in the ICU, as is the use of MV or ECMO when necessary [ 2 , 36 ]. We also observed that epithelial barrier function was severely impaired in the lung biopsy specimen from a patient with laboratory-confirmed H7N9 infection.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, endotracheal intubation and protective mechanical ventilation (MV) have become the mainstay of supportive therapy in the ICU [ 17 , 38 ]. Severe ARDS associated with H7N9 virus infection leads to the use of extracorporeal membrane oxygenation (ECMO), originally applied to support the respiratory function of pediatric patients [ 24 , 36 ]. Nevertheless, approximately 40% of patients do not survive these treatments, possibly because of the following three factors.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies of ECMO treatment for avian influenza A (H7N9) pneumonia are primarily limited to case reports [ 7 – 9 ], and no study has systematically reviewed the efficacy or safety of ECMO to treat such diseases. Therefore, it is particularly important to understand the current application of ECMO for avian influenza A (H7N9) pneumonia-induced severe ARDS, investigate the application timing and management strategies of ECMO, and explore the possible reasons for treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…ECMO can be selected according to the conditions of patients. ECMO can effectively improve oxygenation and plays an important role in rescuing patients with severe H7N9 infection [18,[30][31][32][33][34][35][36][37]. Renal replacement therapy and artificial liver therapy may be used in patients with impending multiple organ dysfunction.…”
Section: Anti-shockmentioning
confidence: 99%